Self-efficacy-based Interventions for Patients With Obstructive Sleep Apnea: A Systematic Review - Min-Eun Cho; Sun-Kyung Hwang (Elsevier, 2024)
SUMMARY: Purpose: This study aimed to systematically review self-efficacy-based interventions for patients with obstructive sleep apnea (OSA) and identify the relationship between the number of used techniques for prompting self-efficacy and the main outcome variables. Methods: This systematic review was conducted in accordance with the PRISMA guidelines. Experimental studies on the use of self-efficacy-based interventions for patients with OSA were analyzed. Five databases, EMBASE, CINAHL, PubMed, SCOPUS, and Web of Science, were systematically searched for articles published until December 2023. Interventions were classified based on the behavior change technique (BCT) taxonomy and the theoretical sources of self-efficacy to conduct a narrative synthesis. Results: Of the 6,968 articles evaluated, 11 were included for analysis (1,304 participants). The results showed that the most frequently employed BCTs in the analyzed studies were "instruction on how to perform a behavior," "exposure," and "social support." Regarding the number of techniques, an average of 6.0 BCTs (range, 4-8) and 3.2 theoretical sources (range, 2-4) were utilized in studies that showed significant improvements in self-efficacy (5 studies), whereas an average of 4.8 BCTs (range, 2-5) and 2.8 theoretical sources (2-3) were used in studies that indicated null results related to self-efficacy (6 studies). Conclusion: This review underscores the potential of self-efficacy-based interventions in the management of OSA and provides a solid theoretical foundation for designing effective interventions. Additionally, the results indicate that utilizing a greater diversity of BCTs and theoretical sources may contribute to the effectiveness of self-efficacy interventions. Therefore, clinicians should consider incorporating various behavior change techniques and four sources of prompting self-efficacy from self-efficacy theory into interventions to enhance self-efficacy, and consequently, treatment adherence in patients with OSA.